Representative national survey on drug use during the COVID-19 stay-at-home order in the USA - Paul Nestadt; Soo-Hoon Lee; Phillip Phan; Bernadette Cullen; Alison Athey; Calliope Holingue; Michelle R Kaufman; Jack Samuels; Tracy Vannorsdall (BMJ Open)
Objectives This study explores the drug use behaviour in the US general population in the early days of the COVID-19 pandemic with a focus on the relationship between sociopsychological factors, mobility restrictions from March to June 2020 and mental health conditions.Design A retrospective anonymous online survey representing a cross-section of the US population in 2020.Setting A qualified panel of 500 000 Qualtrics participants stratified by gender, race, age and geographical region to represent the US population.Participants 3340 participants voluntarily consented to respond.Measures Outcome measure for illicit and non-medical use of prescription drugs based on the National Institute on Drug Abuse-Modified Alcohol, Smoking and Substance Involvement Screening Test Level-2 Substance Use for Adult Questionnaire and predictor measures include self-reports of mobility behaviours, demographics and mental states using psychometrically validated scales.Results χ2 tests showed that those who stayed home reported higher odds (p<0.05) of use across all 10 types of drugs. Logistic regression revealed that those with children at home, larger social circles, and pain, depression or trauma had higher odds, but older individuals and women had lower odds (p<0.05) of drug use.Conclusions Mobility restriction was a risk factor for drug use. Demographics and mental health conditions were important covariates, underscoring the need for further research on unintended consequences of infection control policies during national health crises.